Hospital-Based Violence Intervention Programs (HVIPs): Making a Case for Qualitative Evaluation Designs. (March 2023) - Ranjan, Sheetal; Neudecker, Christine H.; Strange, Catherine Clare; Wojcik, Michelle L. T.; Shah, Aakash; Solhkhah, Ramon
Hospital-based violence intervention programs (HVIPs) are multidisciplinary programs that use a health/public health approach to violence intervention by intervening with victims of violence at the time of injury and leveraging hospital- and community-based resources to address the underlying risk factors for violence. Much of the evidence for the impacts of HVIPs comes from qualitative research, yet there are few reviews of the efficacy of these approaches, and none that focus specifically on the HVIP context. This paper fills this gap by reviewing the common qualitative elements of published HVIP evaluations, and discusses their strengths, challenges, and relative applicability for researchers and practitioners alike. It then sets forth a research agenda, making a case for further (and more varied) qualitative HVIP evaluation research.